THE DYNAMICS OF 1.3-B-D-GLUCAN GIVEN IN THE FORM OF AGARICUS BLAZEI MURILL POWDER TO THE BODY OF WHITE MICE Sprague Dawley AND EFFECT OF RENAL AND HEPATIC HISTOPATHOLOGY - Misgiati Misgiati; Umie Lestari; Aloysius Duran Corebima (The East Java Biological Society, 2013)
Dynamics of compound 1,3-Î²-glucan in Agaricus Blazei Murill (ABM) powder and the effect of renal and hepatic histopathology performed on 24 male rats aged 2 months, were randomly conducted in three treatments there are control, ABM powder, and the pure compound 1.3-Î²-glucan for 28 days. Provision of treatment given in the morning and then 1, 3, 8, 12, and 24 hours after administration of treatment blood was collected, while for urine and feces were collected every 8 hours. Giving treatment was continued until day 28. The results showed that the levels of 1,3-Î²-glucan in pure compounds is higher than the Agaricus Blazei Murill (ABM) powder. The effects on the kidneys and liver histopathology showed that cells necrosis more on pure compounds from the mushroom powder gods, both the kidneys and liver. This study shows that the use of pure compounds to be more careful than Agaricus Blazei Murill (ABM) powder in determining the doses used.